Mucilage exudation facilitates root water uptake in dry soils - Ahmed, Mutez A; Kroener, Eva; Holz, Maire; Zarebanadkouki, Mohsen; Carminati, Andrea (Functional plant biology : FPB, 2014)
As plant roots take up water and the soil dries, water depletion is expected to occur in the rhizosphere. However, recent experiments showed that the rhizosphere was wetter than the bulk soil during root water uptake. We hypothesise that the increased water content in the rhizosphere was caused by mucilage exuded by roots. It is probably that the higher water content in the rhizosphere results in higher hydraulic conductivity of the root–soil interface. In this case, mucilage exudation would favour the uptake of water in dry soils. To test this hypothesis, we covered a suction cup, referred to as an artificial root, with mucilage. We placed it in soil with a water content of 0.03cm3cm-3, and used the root pressure probe technique to measure the hydraulic conductivity of the root–soil continuum. The results were compared with measurements with roots not covered with mucilage. The root pressure relaxation curves were fitted with a model of root water uptake including rhizosphere dynamics. The results demonstrated that when mucilage is added to the root surface, it keeps the soil near the roots wet and hydraulically well conductive, facilitating the water flow from dry soils towards the root surface. Mucilage exudation seems to be an optimal plant trait that favours the capture of water when water is scarce.